Analisis Framing terhadap Pernyataan Resmi Kemenpora RI dan PSSI dalam Kasus Sanksi FIFA terhadap Indonesia - Prastya, Narayana Mahendra (Universitas Muhammadiyah Yogyakarta, 2018)
AbstractThis research aims to know how The Ministry of Youth and Sports Republic of Indonesia (Kemenpora RI) and Indonesian Football Association (PSSI) in FIFA suspension for Indonesia caseThe starting point of this research is crisis could hit every organization. In crisis situation, organization should release official statement to give explanation to public and to save their images. Official statement came from framing process. This research use frame model from Robert N Entman as tools for analysis. The data resources is official statement from Kemenpora RI and PSSI in period April 2015-May 2016. The results are : in define problem and defining causes, both parties are blaming each others. In making moral judgement, both organizations show up their effort to find solution and blaming others with example from football governance in another countires. In treatment recomendation, PSSI focus on the Indonesia national football team, and Kemenpora RI focus on reparation for football managemeng in Indonesia.Keywords : crisis communication, frame analysis, sport communication, sport public relations